(untitled) (Editora Impacto Científico, 2025)
The germination of the seeds is the process by which an embryo plant emerge from dormancy. This development stage of the plants depends on many factors, among which one can include the genetic and environmental nature. Due to lack of information about the percentage and germination speed rate of amaranth seeds (Amaranthus spp), an experiment was carried out under natural conditions on greenhouse (screened with 50% of shading) in Natal-RN, Brazil, from December 26th , 2007 to January 16th, 2008. The experiment was evaluated in a completely randomized design, with five treatments and four replications. In the treatments were utilized the following substrates: Beach Sand (T1), Dune Sand (T2), River Sand (T3), Arisco (rough) Soil (T4) e and Alluvial Soil (T5). The best treatment was T5, it showed 95.56 % of geminated seeds, average time of 11.68 days for germination and better initial development, it was followed by T4. The worst results were noted with treatment T1, which showed 75.56 % of geminated seeds, average time of 12.59 days and minor initial development of the amaranth. DOI: https://doi.org/10.56238/edimpacto2025.090-044